Constrained acetabular liners are a viable option in second-stage re-implantation for chronic infected total hip arthroplasty with abductor or greater trochanter deficiency and large acetabular bone defects - Qiang Xiao; Tingxian Ling; Kai Zhou; Mingcheng Yuan; Bing Xu; Zongke Zhou (BMC Musculoskeletal Disorders, 2022)
Abstract Background Abductor mechanism deficiency is a clear indication for using constrained acetabular liners (CALs), and large acetabular bone defects are considered a relative contraindication to CALs. We report the results of using CALs in special cases in which abductor or greater trochanter deficiency was accompanied by large acetabular bone defects at second-stage re-implantation for chronic infected total hip arthroplasty (THA). Methods Between January 2010 and January 2018, 19 patients who used CALs at second-stage re-implantation and had abductor or greater trochanter deficiency and large acetabular bone defects were included in this study. We followed up with the clinical and radiological results of these patients. Complications and infection-related information were also recorded. Results Eight patients, 4 patients, and 7 patients had Paprosky type IIB, type IIC, and type IIIA acetabular bone defects at second-stage re-implantation, respectively. The indication for using CALs was abductor deficiency in 14 patients and greater trochanter deficiency in the other 5 patients. The mean follow-up was 74.4 months (range 50–96). The mean Harris Hip Score (HHS) was 76.3 points (range 62–86) at the last follow-up. Three patients presented acetabular radiolucent lines with no progress: zone 3, zone 3 and zone 2 and 3, respectively. One patient suffered transient sciatic nerve palsy. There was no dislocation, failure of the CALs, reoperation, or recurrence of infection. Conclusion Our results suggested that for screened patients, CALs are a viable option in second-stage re-implantation for chronic infected THA with abductor or greater trochanter deficiency and large bone defects.